Reconstruction of Planar Multilayered Structures using Multiplicative-Regularized Contrast Source Inversion - Mudrik Alaydrus; Said Attamimi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
There is an increasing interest to have an access to hidden objects without making any destructive action. Such non-destructive method is able to give a picture of the inner part of the structure by measuring some external entities. The problem of reconstructing planar multilayered structures based on given scattering data is an inverse problem. Inverse problems are ill-posed, beside matrix inversion tools, a regularization procedure must be applied additionally. Multiplicative regularization was considered as an appropriate penalty method to solve this problem. The Gauss-Newton inversion method as an optimization procedure was used to find the permittivity values, which minimized some cost functions. Several dielectric layers with different thickness and profiles were observed. Some layers needed more discretization elements and more iteration steps to give the correct profiles.